The Aryl Hydrocarbon Receptor Meets Immunology: Friend or Foe? A Little of Both - Julliard, Walker; Fechner, John H.; Mezrich, Joshua D. (Frontiers in Immunology, 2014)
The aryl hydrocarbon receptor (AHR) has long been studied by toxicologists as a ligand-activated transcription factor that is activated by dioxin and other environmental pollutants such as polycyclic aromatic hydrocarbons (PAHs). The hallmark of AHR activation is the upregulation of the cytochrome P450 enzymes that metabolize many of these toxic compounds. However, recent findings demonstrate that both exogenous and endogenous AHR ligands can alter innate and adaptive immune responses including effects on T-cell differentiation. Kynurenine, a tryptophan breakdown product, is one such endogenous ligand of the AHR. Expression of indoleamine 2,3-dioxygenase by dendritic cells causes accumulation of kynurenine and results in subsequent tolerogenic effects including increased regulatory T-cell activity. At the same time, PAHs found in pollution enhance Th17 differentiation in the lungs of exposed mice via the AHR. In this perspective, we will discuss the importance of the AHR in the immune system and the role this might play in normal physiology and response to disease.